Acetaminophen-induced renal toxicity: preventive effect of silver nanoparticles. Issue 4 (17th June 2020) - Reshi, Mohd Salim; Yadav, Deepa; Uthra, Chhavi; Shrivastava, Sadhana; Shukla, Sangeeta
Abstract: Present study was planned to investigate the ameliorative effect of silver nanoparticles (AgNPs) on acetaminophen-induced nephrotoxicity. Our results demonstrate that therapy of AgNPs at three different doses (50, 100 and 150 μg/kg once only) prevented the acetaminophen (2 g/kg once only) induced acute renal toxicity. AgNPs treated animals also show less intensity in the histological alterations in kidneys and corroborating the results of analysis of serum urea and creatinine. In addition, AgNPs therapy prevented the acetaminophen-induced oxidative stress, which was confirmed by the alleviated lipid peroxidation, enhanced renal reduced glutathione content and restored enzymatic activities of superoxide dismutase, catalase and adenosine triphosphatase in kidney. Thus, our results demonstrate a possible protective potential of AgNPs on renal toxicity induced by acetaminophen. This study will definitely lead to the development of therapeutic drug against nephrotoxicity, after further clinical and preclinical studies. Graphical Abstract: